The yo-yo intermittent recovery test and its relation to the specific position in young soccer players - Losada, J. A.; Fernández, E.; Mora, J. (Archivos de medicina del deporte, 2008)
One of the conditions in the contemporary training is the cumulative assessment of the training process with the help of a suitable test. The endurance of the soccer in competition (creating intermittent driving sequences repeated in time with a high intensity load) requires aerobic and anaerobic metabolic processes, and in turn, are related to the specifi c position to play within the system of play. The assessment of this specifi c endurance of the soccer players, can be done through various tests, offering us the Yo-Yo Intermittent Recovery Test Level 1 (YYIRT1) as a valid tool for assessing the quality. The objective of this research was to relate the results obtained on YYIRT1 in with the specific role played by every young player in the fi eld of play. Material and methods: 16 young soccer players competing in the Division 1 and belonging to the Andalusian Cadet Cádiz CF S.A.D. (15 ± 0.7 years, 66.22 ± 10.43 kg, 173.81 ± 6.82 cm) participated in this study on a voluntary and consensual, like the coaching staff. The test was done in the second period competitive within a mesocycle of conduct and specifi cally in a microcycle adjustment. Results: The results show signifi cant data in terms of distance covered in the YYIRT1 (1987.5 ± 355.59 m.) and its relation to the role play, and the estimated maximum oxygen consumption (53.09 ± 2,98 ml / kg / min). Conclusion: We can deduce that the YYIRT1 is a valid and useful tool for assessing the aerobic condition of young players, because of its intermittent nature, which in turn is related to the specifi c activities of the game.